Foundational and Clinical Science Integration in a Team-Based Learning Module Modeling Care of a Patient With Dyslipidemia - Paul C. Megee; Virginia Uhley; James Grogan; Alan Silverman (Association of American Medical Colleges, 2024)
Introduction Foundational and clinical science integration, a long-standing goal of undergraduate medical education, benefits learners by promoting retention of critical knowledge and skills as well as their transfer to the clinical setting. We implemented a team-based learning (TBL) module in which foundational knowledge and skills from the disciplines of biochemistry, nutrition, and genetics were leveraged in a simulated patient encounter for diagnosis and management of a patient with dyslipidemia. Methods The TBL was deployed in a first-year medical student cardiovascular system course with 125 students over three academic years. Following individual and team readiness assurance tests (iRAT and tRAT, respectively), teams participated in an initial application exercise requiring consideration of clinical and laboratory data and other risk factors to engage the patient in a shared decision-making process. Using dietary and family history narratives in subsequent application exercises, teams completed recommendations for an individualized diet plan and an assessment of potential disease inheritance patterns to formulate appropriate patient care management strategies. Results Student engagement with prelearning materials and session team activities was high as judged by RAT performance and application exercise outcomes: iRAT question performance ranged from 89% to 99% for individual items, and tRAT performance was routinely 100%. Learners reported that the exercises were impactful and believed the learned foundational knowledge and skills were transferable to future patient care. Discussion The dyslipidemia TBL module provides an illustration for early clinical learners of how foundational knowledge and skills can be operationalized and transferred for optimal patient care.